ChemInform Abstract: Deciphering Selectivity in Organic Reactions: A Multifaceted Problem. Issue 28 (June 2016) - Balcells, David; Clot, Eric; Eisenstein, Odile; Nova, Ainara; Perrin, Lionel
Abstract: Review: 46 refs.